Laminated structure, piezoelectric element, electronic device, electronic equipment and system

By forming a compound film on a crystal substrate and laminating epitaxial films with different compositions, the method addresses the adhesion and crystallinity issues in piezoelectric films, resulting in improved piezoelectric properties and electrode quality.

JP7659926B2Active Publication Date: 2025-04-10GAIANIXX INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023576970
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-01-26
Publication Date
2025-04-10
Estimated Expiration
2043-01-26

AI Technical Summary

Technical Problem

Existing piezoelectric films, such as PZT, face challenges with adhesion and crystallinity at the interface, which affect their piezoelectric properties.

Method used

A method involving the formation of a compound film on a crystal substrate, followed by laminating an epitaxial film with a crystalline compound, and then a second epitaxial film with a different composition, to achieve improved adhesion and crystallinity.

Benefits of technology

This approach results in epitaxial films with enhanced adhesion and crystallinity, leading to improved piezoelectric properties and the ability to form high-quality electrodes and laminated structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659926000001
    Figure 0007659926000001
  • Figure 0007659926000002
    Figure 0007659926000002
  • Figure 0007659926000003
    Figure 0007659926000003
Patent Text Reader

Abstract

[Problem] To provide an electrode which comprises an epitaxial film that has good adhesiveness and crystallinity, a laminated structure, an electronic device, and electronic equipment which include the electrode, and production methods which make it possible to obtain the same in an industrially advantageous manner. [Solution] When forming at least a compound film on a crystal substrate, subsequently laminating an epitaxial film that includes a crystalline compound, and further laminating a second epitaxial film of a differing composition from the epitaxial film either directly on the epitaxial film or with another layer therebetween, the second epitaxial film is a single-crystal film having a zero-defect region in an area of not less than 100 nm2 for constituting an electrode, and the epitaxial film is laminated by using a compound element in the compound film to form the epitaxial film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode made of an epitaxial film, a laminated structure, an electronic device, an electronic apparatus, and a method for manufacturing these. [Background technology]

[0002] Thin films made of lead zirconate titanate (Pb(Zr,Ti)O3) (hereinafter referred to as PZT), which has excellent piezoelectric and ferroelectric properties, are used in memory elements such as non-volatile memory (FeRAM), as well as MEMS (Micro Electro Mechanical Systems) technology such as inkjet heads and acceleration sensors, taking advantage of their ferroelectric properties.

[0003] In recent years, it has been studied to form a (200) oriented Pt film on a (100) oriented Si substrate via a (200) oriented ZrO2 film or the like, thereby forming a piezoelectric film with good piezoelectric properties on the Pt film (Patent Document 1). However, the adhesion and crystallinity at the interface are still not satisfactory, and measures to improve the adhesion and crystallinity at the interface and further improve the piezoelectric properties of the piezoelectric film have been awaited. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-154015 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide an electrode made of an epitaxial film having good adhesion and crystallinity, a laminate structure including the electrode, an electronic device, an electronic equipment, and a manufacturing method by which these can be obtained in an industrially advantageous manner. [Means for solving the problem]

[0006] As a result of intensive research to achieve the above object, the present inventors have found that when at least a compound film is formed on a crystal substrate, an epitaxial film containing a crystalline compound is then laminated, and a second epitaxial film having a composition different from that of the epitaxial film is laminated on the epitaxial film directly or via another layer, the crystallinity and adhesion of the second epitaxial film can be dramatically improved by forming the epitaxial film using a compound element in the compound film. They have also found that when the second epitaxial film is formed in this manner, an epitaxial film having excellent adhesion and crystallinity can be easily obtained even if the electrode material is such as Pt. They have found that such an electrode, laminated structure, and manufacturing method can solve the above-mentioned conventional problems at once. Furthermore, after obtaining the above findings, the present inventors conducted further studies and completed the present invention.

[0007] That is, the present invention relates to the following inventions. [1] An electrode including a single crystal film, the single crystal film being 100 nm thick. 2 An electrode having a defect-free region over an area of ​​at least one of the above. [2] The electrode according to [1] above, wherein the thickness of the single crystal film is 100 nm or more. [3] The electrode according to [1] or [2], wherein the single crystal film is a single crystal film of a conductive metal. [4] The electrode according to [3] above, wherein the metal is Pt or a Pt alloy. [5] The electrode according to any one of [1] to [4], wherein the single crystal film has a cubic crystal structure. [6] The electrode according to any one of [1] to [4], wherein the single crystal film has a (100) orientation. [7] A method for manufacturing a laminated structure, comprising forming at least a compound film on a crystal substrate, laminating an epitaxial film containing a crystalline compound, and laminating a second epitaxial film having a different composition from the epitaxial film directly or via another layer on the epitaxial film, the second epitaxial film being 100 nm thick and constituting an electrode. 2 a single crystal film having a defect-free region over an area of ​​at least one of the above, and the epitaxial film is formed by using a compound element in the compound film to form the epitaxial film. [8] The manufacturing method according to [7], further comprising the steps of: using the compound element in the compound film; introducing a compound element gas; and depositing the epitaxial film in the presence of the compound element gas. [9] A laminated structure including at least a first epitaxial film and a second epitaxial film having a composition different from that of the first epitaxial film, the second epitaxial film being an electrode and having a thickness of 100 nm or less. 2 A laminate structure comprising a single crystal film having a defect-free region over an area of ​​at least one of the above.

[10] A piezoelectric element comprising an electrode or a laminated structure, wherein the electrode is the electrode described in any one of [1] to [6] above, and the laminated structure is the laminated structure described in [9] above.

[11] An electronic device comprising an electrode or a laminated structure, wherein the electrode is the electrode described in any one of [1] to [6] above, and the laminated structure is the laminated structure described in [9] above.

[12] The electronic device according to

[11] , which is a piezoelectric device.

[13] An electronic device comprising an electrode, a laminated structure, or an electronic device, wherein the electrode is the electrode described in any one of [1] to [6] above, the laminated structure is the laminated structure described in [9] above, and the electronic device is the electronic device described in

[11] or

[12] above.

[14] A system including an electronic device, characterized in that the electronic device is the electronic device described in

[13] above. Effect of the Invention

[0008] The electrode, the laminated structure, the electronic device, and the electronic device of the present invention include an epitaxial film having good adhesion and crystallinity, and the manufacturing method of the present invention has the effect of making it possible to obtain the electrode, the laminated structure, the electronic device, and the electronic device in an industrially advantageous manner. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of an example of a preferred embodiment of a laminated structure of the present invention. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of another preferred embodiment of the laminated structure of the present invention. [Diagram 3] 1A to 1C are diagrams illustrating an example of an oxide film forming step in a preferred method for producing a laminated structure of the present invention. [Figure 4] 1A to 1C are diagrams illustrating an example of an epitaxial film formation step in a preferred method for producing a laminated structure of the present invention. [Diagram 5] 1 shows cross-sectional STEM images observed in the examples. [Figure 6] 1 shows cross-sectional STEM images observed in the examples. [Figure 7] 1 shows STEM images observed in the examples. [Figure 8] 1 shows STEM images observed in the examples. [Figure 9] 1 is a diagram illustrating a preferred embodiment of a MEMS transducer according to the present invention. [Figure 10] FIG. 1 is a schematic diagram showing an example of a cross-sectional view of a portion of a wafer provided with a piezoelectric actuator, as a suitable application example of the present invention to a fluid discharge device. [Figure 11] 1 shows the results of XRD measurements showing crystal symmetry in an example. [Figure 12] 1 shows the results of XRD measurements showing crystal symmetry in an example. [Figure 13]FIG. 2 is a schematic diagram showing a film forming apparatus preferably used in the examples. [Figure 14] 1 shows a cross-sectional STEM image measured in an example. [Figure 15] 1 shows a STEM image measured in an example. [Figure 16] 1 shows a STEM image of a buried layer measured in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The electrode of the present invention is an electrode including a single crystal film, the single crystal film being 100 nm thick. 2 The feature of this method is that it has a defect-free region over an area of ​​this size or more.

[0011] In the present invention, the thickness of the single crystal film is preferably 10 nm or more, more preferably 50 nm or more, and most preferably 100 nm or more. In such a range, not only the adhesion and crystallinity of the electrode but also the characteristics of the element and the functional film, and even durability can be improved. The upper limit of the film thickness is not particularly limited, but is preferably 100 μm, more preferably 10 μm, and most preferably 1 μm.

[0012] In addition, in the present invention, the single crystal film is preferably a single crystal film of a conductive metal. The conductive metal is not particularly limited as long as it does not impede the object of the present invention, and examples thereof include gold, silver, platinum, palladium, silver-palladium, copper, nickel, and alloys thereof. In the present invention, the conductive metal preferably contains platinum, and more preferably is Pt or a Pt alloy. In addition, in the present invention, the single crystal film preferably has a cubic crystal structure, and the single crystal film is preferably oriented in (100). The crystalline compound is not particularly limited and may be a known crystalline compound, but in the present invention, the crystalline compound is preferably a metal compound, and the metal of the metal compound may also be a known metal. Examples of the metal include metals containing d-block elements in the periodic table. The compound of the metal compound may also be a known compound, and examples of the compound in the crystalline compound include oxides, nitrides, oxynitrides, sulfides, oxysulfides, borides, oxyborides, carbides, oxycarbides, borocarbides, boronitrides, borosulfides, carbonitrides, carbosulfides, and carboborides. In the present invention, oxides or nitrides are preferred because, for example, they can provide better stress relaxation and warpage reduction in heteroepitaxial growth as a buffer layer, and can further provide better electrical properties (particularly the interface between the conductor layer and the insulating layer). In addition, the crystalline compound is preferably a crystalline oxide, the compound film is preferably an oxide film, and the compound element is preferably oxygen. In the present invention, the crystalline compound is preferably a crystalline nitride, the compound film is preferably a nitride film, and the compound element is preferably nitrogen.

[0013] The electrode is formed by forming at least a compound film on a crystal substrate, then laminating an epitaxial film containing a crystalline compound, and further laminating a second epitaxial film having a composition different from that of the epitaxial film directly or via another layer on the epitaxial film, the second epitaxial film being 100 nm thick, which constitutes the electrode. 2The epitaxial film can be easily obtained by forming the epitaxial film by using a compound element in the compound film to form the epitaxial film, and forming the epitaxial film using the compound element in the compound film. Note that, in the laminated structure thus obtained, the epitaxial film is regularly transformed at the interface between the epitaxial film and the second epitaxial film so as to have a lattice constant substantially the same as that of the second epitaxial film, and more specifically, the epitaxial film is transformed at the interface into a mountain-valley structure in which the angles formed by adjacent vertices and bottoms are different from each other.

[0014] Preferred embodiments of the present invention will now be described with reference to the drawings, but the present invention is not limited to these preferred embodiments. Fig. 1 shows a preferred example of the laminated structure, in which an epitaxial layer 3 is laminated on a crystal substrate 1 using an oxide film 2, and a second epitaxial layer 4 is further laminated on the epitaxial layer 3. In this specification, the terms "film" and "layer" may be interchanged depending on the case or situation. In addition, oxides are given as preferred examples of the laminated structure, but the present invention is not limited to these preferred examples, and the present invention can also be suitably applied to various compounds such as nitrides. The laminated structure can be easily manufactured, for example, as shown in Fig. 3, by forming an oxide film 2 of the crystal substrate 1 on the crystal substrate 1, and then forming an epitaxial film 3 made of a crystalline oxide on the crystal substrate 1 using oxygen in the oxide film 2 as shown in Fig. 4, and then forming the second epitaxial film on the epitaxial film 3. In the present invention, the laminated structure may have the oxide film 2 on the crystal substrate 1, but the oxide film 2 may disappear when all the oxygen in the oxide film 2 is taken in during the formation of the epitaxial film 3. Each of these will be described in more detail below, but the present invention is not limited to these specific examples.

[0015] The crystal substrate (hereinafter, simply referred to as "substrate") is not particularly limited as long as the object of the present invention is not hindered, such as the substrate material, and may be a known crystal substrate. It may be an organic compound or an inorganic compound. In the present invention, it is preferable that the crystal substrate contains an inorganic compound. In the present invention, it is preferable that the substrate has crystals on a part or all of the surface, more preferably a crystal substrate having crystals on all or a part of the main surface on the crystal growth side, and most preferably a crystal substrate having crystals on the entire main surface on the crystal growth side. The crystal is not particularly limited as long as the object of the present invention is not hindered, and the crystal structure is not particularly limited, but it is preferable that it is a cubic, tetragonal, trigonal, hexagonal, orthorhombic, or monoclinic crystal, and more preferably a crystal oriented in (100) or (200). In addition, the crystal substrate may have an off angle, and examples of the off angle include an off angle of 0.2° to 12.0°. Here, the "off angle" refers to the angle between the substrate surface and the crystal growth surface. The shape of the substrate is not particularly limited as long as it is plate-like and serves as a support for the epitaxial film. It may be an insulating substrate or a semiconductor substrate, but in the present invention, the substrate is preferably a Si substrate, more preferably a crystalline Si substrate, and most preferably a crystalline Si substrate oriented in (100). In addition to the Si substrate, examples of the substrate material include one or more metals belonging to Groups 3 to 15 of the periodic table or oxides of these metals. The shape of the substrate is not particularly limited, and may be an approximately circular shape (e.g., a circular shape, an elliptical shape, etc.) or a polygonal shape (e.g., a triangular shape, a square shape, a rectangular shape, a pentagonal shape, a hexagonal shape, a heptagonal shape, an octagonal shape, a nonagonal shape, etc.), and various shapes can be suitably used. In addition, in the present invention, a large-area substrate can be used, and the area of ​​the epitaxial film can be increased by using such a large-area substrate.

[0016] In the present invention, the crystal substrate preferably has a flat surface, but it is also preferable that the crystal substrate has an uneven shape on a part or all of the surface, since this can improve the quality of the crystal growth of the epitaxial film. The crystal substrate having the uneven shape may have an uneven portion consisting of a concave or convex portion formed on a part or all of the surface, and the uneven portion is not particularly limited as long as it is composed of a convex portion or a concave portion, and may be an uneven portion consisting of a convex portion, an uneven portion consisting of a concave portion, or an uneven portion consisting of a convex portion and a concave portion. The uneven portion may be formed of regular convex portions or concave portions, or may be formed of irregular convex portions or concave portions. In the present invention, it is preferable that the uneven portion is formed periodically, and it is more preferable that the uneven portion is patterned periodically and regularly. The shape of the uneven portion is not particularly limited, and examples thereof include a stripe shape, a dot shape, a mesh shape, and a random shape, but in the present invention, a dot shape or a stripe shape is preferable, and a dot shape is more preferable. In addition, when the unevenness is patterned periodically and regularly, the pattern shape of the unevenness is preferably a polygonal shape such as a triangle, a quadrangle (for example, a square, a rectangle, or a trapezoid), a pentagon, or a hexagon, a circle, or an ellipse. In addition, when the unevenness is formed in a dot shape, the lattice shape of the dots is preferably a lattice shape such as a square lattice, an oblique lattice, a triangular lattice, or a hexagonal lattice, and more preferably a triangular lattice shape. The cross-sectional shape of the concave or convex part of the unevenness is not particularly limited, but examples thereof include a U-shape, a U-shape, an inverted U-shape, a wave shape, or a polygonal shape such as a triangle, a quadrangle (for example, a square, a rectangle, or a trapezoid), a pentagon, or a hexagon. In addition, the thickness of the crystal substrate is not particularly limited, but is preferably 50 to 2000 μm, and more preferably 100 to 1000 μm.

[0017] The oxide film is not particularly limited as long as it is an oxide film capable of incorporating oxygen atoms into the epitaxial film, and usually includes an oxide material. The oxide material is not particularly limited as long as it does not impede the object of the present invention, and may be a known oxide material. Examples of the oxide material include oxides of metals or semimetals. In the present invention, it is preferable that the oxide film includes the oxide material of the crystal substrate, and examples of such oxide films include a thermal oxide film and a natural oxide film of the crystal substrate. In addition, in the present invention, the oxide film may be a sacrificial layer in which a part or all of the film disappears or is destroyed when oxygen atoms are incorporated, and in the present invention, it is preferable that the oxide film is an oxygen supply sacrificial layer in which oxygen atoms are incorporated and the oxide film itself disappears during the crystal growth of the epitaxial layer. In addition, the oxide film may be patterned, for example, in a striped, dotted, meshed, or random pattern. The thickness of the oxide film is not particularly limited, but is preferably more than 1 nm and less than 100 nm.

[0018] The epitaxial layer preferably includes an epitaxial film incorporating oxygen atoms from the oxide film. The phrase "epitaxial film incorporating oxygen atoms from the oxide film" means that oxygen atoms from the oxide film are taken by the epitaxial film during the crystal growth of the epitaxial film. The epitaxial film is not particularly limited as long as it is an epitaxial film that has been crystal-grown by incorporating oxygen atoms from the oxide film, but in the present invention, it is preferable that the epitaxial film includes a metal or a metal oxide. The metal is preferably, for example, one or more metals belonging to the d block of the periodic table. The metal oxide is preferably, for example, one or more oxides of metals belonging to the d block of the periodic table. In the present invention, the epitaxial film preferably includes a dielectric. In addition, in the present invention, the epitaxial film preferably includes a neutron absorbing material. The neutron absorber may be a known neutron absorber, and in the present invention, by using such a neutron absorber to capture oxygen from the oxide film, it is possible to improve adhesion, crystallinity, and further the properties of the functional film. A suitable example of the neutron absorber is hafnium (Hf). The epitaxial layer may be composed of one or more types of epitaxial films, and in the present invention, it is preferable that the epitaxial layer includes two or more types of the epitaxial films. More specifically, for example, it is preferable that a second epitaxial film having a composition different from that of the epitaxial film is laminated on the epitaxial film directly or via another layer. By stacking in this manner, the first epitaxial layer can be regularly transformed at the interface between the epitaxial layer (hereinafter also referred to as the "first epitaxial layer" or "first epitaxial film") and the second epitaxial layer so that the lattice constant of the first epitaxial layer becomes approximately the same as that of the second epitaxial layer.As a preferred example of the regular transformation, for example, a transformation in which the shape is transformed into a mountain-valley structure is given. In the present invention, it is preferable that the angles formed by the adjacent vertices and bottoms of the mountain-valley structure are different from each other, and it is more preferable that each of the angles is within the range of 30° to 45°. Here, the epitaxial layer usually has a first crystal face and a second crystal face, and since the transformation may cause a lattice constant difference between the first crystal face and the second crystal face, it is preferable that the lattice constant difference between the first crystal face and the second crystal face is within the range of 0.1% to 20%. In the present invention, since the first crystal face can be made substantially the same as the lattice constant of the second epitaxial film, it is easy to realize that the lattice constant difference between the first epitaxial layer and the second epitaxial layer is within the range of 0.1% to 20%.

[0019] In addition, a laminated structure including at least a first epitaxial film and a second epitaxial film having a composition different from that of the first epitaxial film, the second epitaxial film being an electrode and having a thickness of 100 nm or less, 2 The present invention also encompasses a laminate structure that is a single crystal film having a defect-free region in the above area.

[0020] In the present invention, it is more preferable that the first epitaxial film is a dielectric and the second epitaxial film is an electrode. By using the second epitaxial layer as an electrode, not only can the adhesion and crystallinity at the interface be improved, but also, for example, the characteristics of the element can be improved. In addition, according to the present invention, when the second epitaxial layer is made of a single crystal film of a conductive metal, a large-area defect-free film can be easily obtained, and not only the function as an electrode but also the characteristics of the element can be improved. The conductive metal is not particularly limited as long as it does not impede the object of the present invention, and examples thereof include gold, silver, platinum, palladium, silver-palladium, copper, nickel, and alloys thereof, but in the present invention, it is preferable that it contains platinum. In addition, in the present invention, according to the above-mentioned manufacturing method, it is preferable to obtain a film having a thickness of 100 nm or more. 2A defect-free single crystal film can be obtained as an electrode with an area of ​​1000 nm or more. 2 A defect-free single crystal film can be easily obtained with the above area. Also, a single crystal film having a thickness of preferably 100 nm or more can be easily obtained as an electrode.

[0021] In the present invention, it is preferable that a third epitaxial film and / or a fourth epitaxial film having a composition different from that of the second epitaxial film is laminated on the second epitaxial film directly or via another layer. Fig. 2 shows a preferred example of a laminated structure in which the third epitaxial layer 5 and the fourth epitaxial layer 6 are laminated on the second epitaxial layer 4. In the laminated structure of Fig. 2, a first epitaxial layer 3 is laminated on a crystal substrate 1 using an oxide film, and further, a second epitaxial layer 4 is laminated on the first epitaxial layer 3, a third epitaxial layer 5 is laminated on the second epitaxial layer 4, and a fourth epitaxial layer 6 is laminated on the third epitaxial layer 5. The third epitaxial film in the third epitaxial layer is preferably a dielectric, a semiconductor or a conductor, more preferably a dielectric, and most preferably a piezoelectric. The fourth epitaxial film in the fourth epitaxial layer is preferably a dielectric, a semiconductor or a conductor, more preferably a dielectric, and most preferably a piezoelectric. The thickness of each of the epitaxial films is not particularly limited, but is preferably 10 nm to 100 μm, and more preferably 50 nm to 30 μm.

[0022] In the method for producing the laminated structure, in which an epitaxial layer is laminated on a crystal substrate via at least an oxide film, the laminated structure is preferably formed by forming an epitaxial film using oxygen atoms in the oxide film at 350° C. to 700° C. If the temperature is within the range of 350° C. to 700° C., the oxygen atoms in the oxide film can be easily incorporated into the epitaxial film to cause crystal growth.

[0023] In the present invention, it is preferable to form the epitaxial film by using oxygen gas after using oxygen atoms in the oxide film, and the film formation rate is improved by forming the epitaxial film in this manner. Also, by forming the film in this manner, a laminated structure in which an epitaxial layer is laminated on a crystal substrate, and a laminated structure having an amorphous thin film containing a constituent metal of the epitaxial layer and / or the crystal substrate and / or a buried layer containing the constituent metal and embedded in a part of the crystal substrate, which is one or more, can be easily obtained. In the present invention, it is preferable that the laminated structure has both the amorphous layer and the buried layer, since the functionality of the epitaxial film can be further improved. Also, it is preferable that the amorphous layer and the buried layer each contain a constituent metal of the epitaxial layer, since the crystallinity of the epitaxial film is further improved. In the present invention, it is preferable that the constituent metal contains Hf, since this further promotes stress relaxation and further enables stress relaxation in multiple stages. In the present invention, it is preferable that the amorphous thin film has a thickness of 1 nm to 10 nm, since this can further improve the crystallinity of the epitaxial film, and an amorphous thin film having such a preferable thickness can be easily obtained by the preferred manufacturing method of the present invention. In the present invention, it is preferable that the buried layer has a cross-sectional shape of an approximately inverted triangle, since this can further improve the functionality of the epitaxial film. These preferable laminated structures can be easily obtained by appropriately adjusting the thickness of the oxide film and the timing of introducing the oxygen gas.

[0024] As the lamination means used in the lamination, the deposition means for the epitaxial film is usually preferably used, and the deposition means may be a known deposition means. In the present invention, the deposition means is preferably vapor deposition or sputtering, and more preferably vapor deposition.

[0025] The crystal film or laminated structure obtained as described above is suitably used in electronic devices according to a conventional method. For example, the laminated structure can be connected to a power source or an electric / electronic circuit as a piezoelectric element, and mounted on a circuit board or packaged to form various electronic devices. In the present invention, the electronic device is preferably a piezoelectric device, and can be used as a piezoelectric device in electronic devices such as inkjet printer heads, microactuators, gyroscopes, and motion sensors. In addition, for example, if an amplifier and a rectifier circuit are connected and packaged, it can be used in various sensors such as magnetic sensors. It can also be applied to constant voltage driven memories, and for example, if a storage element and a rectifier power management circuit are connected, it becomes an energy conversion device (energy harvester) that generates power from an external magnetic field or vibration. The energy conversion device is incorporated and used in power supply systems and wearable terminals (earphones / hearable devices, smart watches, smart glasses (eyeglasses), smart contact lenses, cochlear implants, cardiac pacemakers, etc.). In the present invention, the laminated structure is preferably used in, for example, smart glasses, AR headsets, MEMS mirrors for LiDAR systems, piezoelectric MEMS ultrasonic transducers (PMUTs) for advanced medical applications, and piezo heads for commercial and industrial 3D printers.

[0026] The electronic device is suitably used in electronic devices in the usual manner, and can be applied to various electronic devices other than the above-mentioned electronic devices, and more specifically, suitable examples include liquid ejection heads, liquid ejection devices, vibration wave motors, optical devices, vibration devices, imaging devices, piezoelectric acoustic parts, audio playback devices having the piezoelectric acoustic parts, audio recording devices, mobile phones, various information terminals, and the like.

[0027] Furthermore, the electronic device is also applied to a system in the usual manner, and an example of such a system is a sensor system. EXAMPLES

[0028] Example 1 The crystal growth surface side of the Si substrate (100) was treated by RIE, and then heated in the presence of oxygen to form a thermal oxide film. Then, without using oxygen, a metal from the deposition source was thermally reacted with oxygen in the oxide film on the Si substrate by vapor deposition to form a single crystal of crystalline metal oxide on the Si substrate. Next, oxygen was introduced, the temperature was lowered, and the pressure was increased, and a single crystal film of crystalline metal oxide was formed by vapor deposition. The conditions of the vapor deposition method during this film formation were as follows: Vapor deposition source: Hf, Zr Voltage: 3.5~4.75V Pressure: 3×10 -2 ~6×10 -2 Pa Substrate temperature: 450~700℃

[0029] Next, a platinum (Pt) metal film was formed as a conductive film constituting an electrode on the single crystal film of the crystalline metal oxide by sputtering under the following conditions. Equipment: ULVAC sputtering equipment QAM-4 Pressure: 1.20×10 -1 Pa Target: Pt Power: 100W(DC) Thickness: 100nm Substrate temperature: 450~600℃

[0030] Next, an SRO film was formed on the conductive film by sputtering under the following conditions. Equipment: ULVAC sputtering equipment QAM-4 Power: 150W(RF) Gas: Ar Pressure: 1.8Pa Substrate temperature: 600℃ Thickness: 20nm

[0031] Next, a Pb(Zr 0.52 Ti 0.48 The conditions for this are as follows:

[0032] Lead acetate was used as the raw material for Pb, zirconyl nitrate was used as the raw material for Zr, and titanium isopropoxide was used as the raw material for Ti. The raw materials for Pb, Zr, and Ti were mixed to a composition ratio of Pb:Zr:Ti=100+δ:52:48, and the solvent was pure water in consideration of the solubility of the raw materials, with acetic acid added to control hydrolysis. Furthermore, ethanol (0.5-3.0 mol per 1 mol of PZT) in which polyvinylpyrrolidone powder had been mixed and dissolved was added to adjust the viscosity. Finally, an appropriate amount of 2n-butoxyethanol was mixed to adjust the wettability during application, and a sol-gel solution was prepared as the raw material solution.

[0033] Next, the prepared sol-gel solution was dropped onto a substrate and rotated at 2000 rpm for 1 minute to spin coat (apply) the sol-gel solution onto the substrate to form a film containing the precursor. The substrate was then placed on a hot plate at 150°C, and then placed on a hot plate at 350°C to evaporate the solvent and dry the film. This process was repeated five times to stack five layers under the same conditions, and then the precursor was oxidized and crystallized by heat treatment at 650°C for 3 minutes in an oxygen (O2) atmosphere. The above process was repeated 10 times to obtain Pb(Zr 0.52 Ti 0.48 The total thickness of the film was 10 μm.

[0034] The obtained laminated structure was a laminated structure including electrodes having good adhesion and crystallinity. In addition, cross-sectional STEM images of the obtained laminated structure are shown in Figs. 5 and 6. It can be seen from Fig. 6 that a very good laminated structure was obtained, and in particular, in Fig. 5, it can be seen that a regular mountain-valley structure is provided at the interface between the single crystal film of the crystalline metal oxide and the conductive film, and the angles formed by the adjacent vertices and bottom points of the mountain-valley structure are different within the range of 30° to 45°. In addition, X-ray crystal lattice images of the conductive film are shown in Figs. 7 and 8. From Figs. 7 and 8, it can be seen that a defect-free large-area conductive film is obtained, and it can be seen that it exhibits excellent effects in terms of electrode characteristics and the piezoelectric characteristics of the piezoelectric film laminated thereon. Conventionally, it has been difficult for a piezoelectric film formed by spin coating to exhibit piezoelectric characteristics, but the piezoelectric film (PZT film) formed by spin coating in this embodiment had good piezoelectric characteristics. In addition, the crystals of the crystalline substrate of the laminated structure, the single crystal film of the crystalline metal oxide, and the conductive film were measured using an X-ray diffraction device. The results of the XRD measurements are shown in Figure 11. As is clear from Figure 11, a (Hf, Zr)O2 film and a Pt single crystal film having good crystallinity were formed on the Si crystal substrate.

[0035] Example 2 A platinum (Pt) metal film was formed as a conductive film on the single crystal film of the crystalline metal nitride in the same manner as in Example 1, except that nitrogen gas was used instead of oxygen gas. Then, the crystal substrate of the laminated structure, the single crystal film of the crystalline metal nitride, and the conductive film were each measured using an X-ray diffraction device. FIG. 12 shows the XRD measurement results. As is clear from FIG. 12, a (Hf, Zr)N film and a Pt single crystal film having good crystallinity were formed on the Si crystal substrate. When measured by a four-terminal method, the obtained single crystal film of the crystalline metal nitride had good conductivity.

[0036] The deposition apparatus used in forming the single crystal of the crystalline metal oxide in Example 1 is shown in Fig. 13. The deposition apparatus in Fig. 13 includes at least metal sources 101a-101b in a crucible, earths 102a-102h, ICP electrodes 103a-103b, cut filters 104a-104b, DC power sources 105a-105b, RF power sources 106a-106b, lamps 107a-107b, Ar source 108, reactive gas source 109, power source 110, substrate holder 111, substrate 112, cut filter 113, ICP ring 114, vacuum chamber 115, and rotation shaft 116. The ICP electrodes 103a-103b in Fig. 13 have a substantially concave curved shape or a parabolic shape curved toward the center of substrate 112.

[0037] As shown in Fig. 13, the substrate 112 is fixed on the substrate holder 111. Next, the rotating shaft 116 is rotated using the power supply 110 and a rotating mechanism (not shown) to rotate the substrate 112. The substrate 112 is heated by the lamps 107a-107b, and the inside of the vacuum chamber 115 is evacuated to a vacuum or reduced pressure by a vacuum pump (not shown). Thereafter, Ar gas is introduced from the Ar source 108 into the vacuum chamber 115, and argon plasma is formed on the substrate 112 using the DC power supplies 105a-105b, the RF power supplies 106a-106b, the ICP electrodes 103a-103b, the cut filters 104a-104b, and the earths 102a-102h, thereby cleaning the surface of the substrate 112.

[0038] Ar gas is introduced into the vacuum chamber 115, and a reactive gas is introduced using a reactive gas source 109. At this time, lamps 107a to 107b, which are lamp heaters, are alternately turned on and off, so that a crystal growth film of better quality can be formed.

[0039] A STEM analysis was performed on the single crystal film (epitaxial layer) of the crystalline metal oxide on the crystal substrate in the laminated structure obtained in the same manner as in Example 1. The results are shown in Figs. 14 to 16. From Fig. 14, it can be seen that the buried layer 1004 is formed between the crystal substrate 1011 and the epitaxial layer 1001, and further, the amorphous layers 1002 and 1003 are formed. From Fig. 15, it can be seen that the first amorphous layer 1002 on the crystal substrate 1011 contains Si of the crystal substrate and Zr, which is a constituent metal of the epitaxial layer 1001. From Fig. 16, it can be seen that the buried layer 1004 has a cross-sectional shape of a substantially inverted triangle, and is an oxide containing Hf and Si.

[0040] (Examples) Preferred application examples of the electrodes contained in the obtained laminated structure will be described in more detail below with reference to the drawings, but the present invention is not limited to these application examples. In the present invention, unless otherwise specified, a piezoelectric device or the like can be manufactured from the laminated structure by using known means.

[0041] 9 shows an embodiment of an acoustic MEMS transducer constituting a MEMS microphone in which the laminated structure of the present invention is preferably used. The MEMS transducer can constitute an acoustic emission device (for example, a speaker, etc.).

[0042] The MEMS microphone composed of the acoustic MEMS transducer in FIG. 9 shows a cantilever type MEMS microphone, and includes a Si substrate 21 having two cantilever beams 28A, 28B and a cavity 30. Each of the cantilever beams 28A, 28B is fixed to the substrate 21 at each end, and a gap 9 is provided between the cantilever beams 8A, 8B. The cantilever beams 8A, 8B are formed by a laminated structure including, for example, a plurality of piezoelectric layers (PZT films) 26a, 26b, which are alternated with a plurality of electrode layers, i.e., Pt films 24a, 24b, 24c and SRO films 25a, 25b, 25c, 25d. A dielectric layer (single crystal film of crystalline oxide) 23 electrically insulates the cantilever beams 8A, 8B from the crystal substrate 21. In FIG. 9, a neutron absorbing material (e.g., HfO2 or its mixed crystal) is used for the dielectric layer (single crystal film of a crystalline oxide) 23, which has superior adhesion to the Si substrate and crystallinity compared to cases where SiO2, SiN, etc. are used, and furthermore, has superior piezoelectric properties and durability.

[0043] FIG. 10 shows an example of application to a fluid ejection device that can be used in printing applications, particularly in the form of an inkjet printhead, in which the laminated structure of the present invention is preferably used, and specifically shows a cross-sectional view of a portion of a wafer having a piezoelectric actuator including Pt films 34a, 34b and SRO films 35a, 35b as electrode layers and a PZT film 36 as a piezoelectric film. In addition to the piezoelectric actuator, the wafer of FIG. 10 also includes a chamber 41 for containing a fluid. The chamber 41 is configured to take in a fluid from a tank (not shown) through a flow path 40. The wafer of FIG. 10 also includes a Si substrate 31, on which a dielectric layer (single crystal film of a crystalline oxide) 33 is provided as a first epitaxial layer, facing the chamber 41. 10, a neutron absorbing material (e.g., HfO2 or its mixed crystal) is used for the dielectric layer (single crystal film of crystalline oxide) 23, which has superior adhesion to the Si substrate and crystallinity as well as superior piezoelectric properties and durability compared to the case of using SiO2, SiN, etc. Note that the single crystal film of crystalline oxide 33 has, for example, a quadrangular shape in a top view (not shown), and such a shape may be any of, for example, a square, a rectangle, a rectangle with rounded corners, a parallelogram, etc.

[0044] On the single crystal film 33 of the crystalline oxide, a Pt film 34a, an SRO film 35a, a piezoelectric film (PZT film) 36, an SRO film 35b, and a Pt film 34b are laminated in this order to form a piezoelectric actuator. The piezoelectric actuator further includes an insulating film 37 extending on the electrodes 34a and 35a, the piezoelectric film 36, and the electrodes 34b and 35b. The insulating film 37 includes a dielectric material used for electrical insulation, and such a dielectric material may be a known dielectric material, for example, a SiO2 layer, a SiN layer, or an Al2O3 layer. The thickness of the insulating layer including the insulating film as a constituent material is not particularly limited, but is preferably between about 10 nm and about 10 μm. The conductive path 39 is provided on the insulating layer (insulating film) 37 and contacts the electrodes 34a and 35a and the electrodes 34b and 35b, respectively, to enable selective access during use. The conductive path may be made of a known conductive material, and a suitable example of such a conductive material is aluminum (Al). The passivation layer 42 is provided on the insulating layer 37, the electrodes 34b and 35b, and the conductive path 39. The passivation layer 42 may be made of a dielectric material used for passivation of the piezoelectric actuator, and the dielectric material is not particularly limited and may be a known dielectric material. Suitable examples of the dielectric material include SiN and SiON (silicon oxynitrate). The thickness of the passivation layer is not particularly limited, but is preferably between about 0.1 μm and about 3 μm. The conductive pad 38 is also provided along the piezoelectric actuator and is electrically connected to the conductive path 39. The passivation layer 42 functions as a barrier layer that protects the piezoelectric body from moisture and the like. [Industrial Applicability]

[0045] The electrode of the present invention is suitably used as an electronic device such as a piezoelectric device, and is suitably used in electronic equipment, sensor systems, and the like. [Explanation of symbols]

[0046] 1. Crystal Substrate 2. Oxide film 3 (First) Epitaxial Layer 4 Second epitaxial layer 5. Third epitaxial layer 6 Fourth epitaxial layer 11. Silicon substrate 13 Single crystal film of crystalline oxide 14 Conductive film 15 SRO membrane 16 PZT membrane 21 Crystalline substrate (Si substrate) 23 (First) epitaxial layer (single crystal film of crystalline oxide) 24a Second epitaxial layer (Pt film) 24b Sixth epitaxial layer (Pt film) 24c 10th epitaxial layer (Pt film) 25a Third epitaxial layer (SRO film) 25b Fifth epitaxial layer (SRO film) 25c Seventh epitaxial layer (SRO film) 25d 9th epitaxial layer (SRO film) 26a Fourth epitaxial layer (PZT film) 26b Eighth epitaxial layer (PZT film) 28A Cantilever Beam 28B Cantilever beam 29 Gap 30 cavities 31 Crystalline substrate (Si substrate) 33 (First) epitaxial layer (single crystal film of crystalline oxide) 34a Second epitaxial layer (Pt film) 34b Sixth epitaxial layer (Pt film) 35a Third epitaxial layer (SRO film) 35b Fifth epitaxial layer (SRO film) 36 Fourth epitaxial layer (PZT film) 37 Insulating Film 38 Conductive Pad 39 Conductive Path 40 Flow Path 41 Chamber 42 Passivation Layer 101a~101b Metal source 102a~102j Earth 103a~103b ICP electrode 104a~104b Cut Filter 105a~105b DC power supply 106a~106b RF power supply 107a~107b Lamps 108 Ar source 109 Reactive Gas Sources 110 Power supply 111 PCB Holder 112 Substrate 113 Cut Filter 114 ICP Ring 115 Vacuum chamber 116 Rotational Axis 1001 Epitaxial layer 1002 First amorphous layer 1003 Second amorphous layer 1004 Buried Layer 1011 Board

Claims

1. A laminated structure having at least a crystalline substrate which is a Si substrate, a first epitaxial film which is a metal oxide containing Hf and Zr, and a second epitaxial film having a composition different from that of the first epitaxial film, a first amorphous layer formed between the crystal substrate and the first epitaxial film and containing Zr and Si; a second amorphous layer formed between the first amorphous layer and the first epitaxial film, the second amorphous layer including Hf, Zr and Si; one or more buried layers embedded in a portion of the crystal substrate and containing Hf and Si; having The second epitaxial film is an electrode, a Pt metal film, and has a thickness of 100 nm. 2 a single crystal film having a defect-free region in an area of ​​at least The buried layer has a cross-sectional shape of a substantially inverted triangle.

2. A regular peak-valley structure is provided at an interface between the first epitaxial film and the second epitaxial film, 2. The laminated structure according to claim 1, wherein the angles formed by adjacent vertices and bottoms of the peak-valley structure are different and fall within a range of 30° to 45°.

3. A laminated structure as described in claim 1, wherein a peak-valley structure is provided at the interface between the second amorphous layer and the first epitaxial film.

4. A piezoelectric element including a laminated structure, characterized in that the laminated structure is a laminated structure described in any one of claims 1 to 3.

5. An electronic device including a laminated structure, characterized in that the laminated structure is a laminated structure described in any one of claims 1 to 3.

6. 6. The electronic device of claim 5 which is a piezoelectric device.

7. An electronic device including a laminated structure, characterized in that the laminated structure is a laminated structure described in any one of claims 1 to 3.

8. A system including an electronic device, the electronic device being the electronic device according to claim 7.

Citation Information

Patent Citations

  • Forming method of dielectric film

    JP2004006960A

  • Ferroelectric ceramic and method for manufacturing the same

    JP2015154015A

  • Film structure and manufacturing method of the same

    JP2019216181A

  • Piezoelectric element, inkjet head, inkjet printer and method for producing piezoelectric element

    WO2015064341A1

  • Film structure, piezoelectric film and superconductor film

    WO2020179210A1